A UK national study of prevalence and correlates of adopting or not adopting a recovery identity among individuals who have overcome a drug or alcohol problem - Ed Day; Ifigeneia Manitsa; Amanda Farley; John F. Kelly (Substance Abuse Treatment, Prevention, and Policy, 2023)
Abstract Background The concept of recovery has increasingly become an organizing paradigm in the addiction field in the past 20 years, but definitions of the term vary amongst interested groups (e.g. researchers, clinicians, policy makers or people with lived experience). Although professional groups have started to form a consensus, people with lived experience of alcohol or drug (AOD) problems use the term in a different way, leading to confusion in policy making in the UK. Greater knowledge about the prevalence and correlates of adopting a recovery identity amongst those who have overcome an AOD problem would inform clinical, public health, and policy communication efforts. Methods We conducted a cross-sectional nationally representative survey of individuals resolving a significant AOD problem (n = 1,373). Weighted analyses estimated prevalence and tested correlates of label adoption. Qualitative analyses summarized reasons for adopting or not adopting a recovery identity. Results The proportion of individuals currently identifying as being in recovery was 52.4%, never in recovery 28.6%, and no longer in recovery 19.0%. Predictors of identifying as being in recovery included current abstinence from AOD, formal treatment, recovery support service or mutual-help participation, and history of being diagnosed with AOD or other psychiatric disorders. Qualitative analyses found themes around not adopting a recovery identity related to low AOD problem severity, viewing the problem as resolved, or having little difficulty in stopping. Conclusions Despite increasing use of the recovery label and concept in clinical and policy contexts, many resolving AOD problems do not identify in this manner. These are most likely to be individuals with less significant histories of impairment secondary to AOD and who have not engaged with formal or informal treatment systems. The understanding of the term recovery in this UK population did not completely align with abstinence from alcohol or drugs.